Pentingnya Pengetahuan Mengenai Anemia Remaja Putri di SMA N 1 Tanjung Jabung Barat - Arnati Wulansari; Siti Aminah; Rahmadiani Rahmadiani (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
The low khowledge of teenager girl at SMA N 1 Tanjung Jabung Barat was one of the reason for distribution of iron supplemented tablets from Dinas Kesehatan Tanjung Jabung Barat. In addition, knowledge about iron supplemented tablets is also very minimal. So it is not uncommon for many reason that iron supplemented tablets are not consumed and are not properly distributed.one of efforts to overcome this problem is counseling about anemia. This activity was carried out at SMA N 1 Tanjung Jabung Barat. The implementation of this activity is from September 2020 to February 2021. The target of this activity is teenager girl of SMA N 1 Tanjung Jabung Barat. The implementation method are in the form of counseling and discussion. The results obtained in this activity were the goal of understanding the material about anemia. It is recommended that the school be able to work together with Puskesmas and Dinas Kesehatan to provide health education regularly when carry out activities to provide iron supplement tablets in order to understand the importance of knowledge about anemia